(untitled) (Eurasian Journal of Ecology, 2016)
Data on species composition, dominant groups, abundance and biomass of benthic macro invertebrates of Bukhtarma reservoir in 2005¬2009 are given. About 66 species are determined. Three species - Borystenia naticina, Agraylea multipunctata and Tipula pierrei are recorded in Bukhtarma reservoir for the first time. Oligochaetes, larvae of chironomids and mollusks dominated.